Inmate Responses to Correctional Officer Deviance: A Model of Its Dynamic Nature. Issue 2 (2nd April 2016) - Ross, Jeffrey Ian; Tewksbury, Richard; Rolfe, Shawn M.
ABSTRACT: The relationship between correctional officers (COs) and prisoners is dynamic and bounded by a unique context. COs engage in numerous sanctioned and unsanctioned behaviors within their correctional institution. The latter actions are typically referred to as deviant behavior. COs' deviance can have a debilitating effect not only on other officers, correctional workers, the administration, but also inmates and the institution as a whole. This article specifies a model of the interaction between COs' deviance and inmate reactions to these kinds of behaviors. In general, the study argues that convicts can respond in four different, but interrelated ways: obedience or deference to authority, apathy, adaptation, and resistance. Acts of prisoners resisting can further lead to COs' deviant behaviors to continue within the correctional institution.